Um lugar do tamanho do mundo: socialidade e narrativas do Serviluz - Campos, José Tiago de Queiroz Mendes (2012)
This dissertation is an ethnography of the sociality forms of Serviluz. Its conducting wire is the narrative of cultural segments through which the researcher sought to capture the social relations heterogeneity of the colaborators of this research. It strives to elucidate symbolic elements that act in the dynamics of the network woven by them. This research moves away from the position of dominant discourse, using Bruno Latour’s principles of symmetrical Antropology and Roy Wagner’s teachings, which propose the very culture as tool to think reality. The goal is to uncover other possible worlds. Therefore, Serviluz is presented retrospectivelly, and followed by the narrative of experiences in the work field. A search for identification of the forms of sociality networks succeeds the narrative, in an attempt to show perspectives and significations shared by men of the sea, sportsmen, men and women associations, garbage pickers, religious people, drug addicts, and others. Interviews collected from Serviluz inhabitants and witnessing their day-to-day activities during one month housing there were the main source of this research. This experience evidenced that, apart from stereotypes, the dynamics of sociality of Serviluz is substantially composed of scape lines of human drama. In Serviluz one might move from war to solidarity, from solitude to street gossip, from drug addiction to contemplation of nature. The tension arose from the intersection of these multiple trajectories produces the integrative character of Serviluz. Its network dynamics therefore cannot be reduced to categorizations.